Early Complications of Modified Tension-Band Wiring (MTBW) in the Treatment of Close Patellar Fractures - Ghareeb Ullah, Mohammad Ishaq, Muhammad Hanif, Kamran Saeed, Usmanullah, Jamshed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Patella fracture account for 1 Percent of all skeletal fracture, Patella fractures are problematic because the loss of the extensor mechanism of the knee, loss of articular congruity and stiffness of the knee joint. The surgical goals are anatomic reconstruction of the articular surface and stable fixation to allow early motion. Modified tension band wiring MTBW (MTBW) is the procedure of choice for patellar fracture these days because of the dramatic decrease in post-operative complications with this procedure.The complications noted in the early post-operative period are infection,loss of reduction, prominence of hardware, and knee stiffness. Objective: To determine the frequency of early post-operative complications following modified tension band wiring MTBW for closed patellar fractures. Methods: This study was conducted in the department of orthopedic surgery, Lady Reading Hospital, Peshawar from June 2010-september 2011. Through a descriptive cross sectional study, a total of hundred patients of closed patellar fractures were selected in a consecutive manner from the OPD and ER department. All patients were subjected to modified tension band wiring MTBW under G/A by an expert orthopedic surgeon and data was also collected at 1st week, 1st month, 3 months and 6 months regarding early post-operative complications like loss of reduction, infection, prominence of hardware and stiffness. Results: Total patients were hundred. There were 60 (60 Percent) males and 40 (40 Percent) were females. Mean age of the patients was 43.82 years + 14.3SD years (range 20-85 years). 74 (74 Percent) were presented with history of road traffic accident. Overall complication rate by the end of 6 months was a total of 25 Percent with of 21 Percent patients with infection, 11 Percent had developed stiffness, 6 Percent with hardware prominence and only 4 Percent with loss of reduction. Conclusion: The frequency of early post-operative complication following modified tension band wiring MTBW for closed patellar fractures was higher than previously reported and further research work should be carried out to identify the factors responsible for it. Keywords: Developed Stiffness, Closed Fracture Patella, Modified Tension Band Wiring MTBW, Early Post-Operative Complications, Hardware Prominence,